Standardisation and quality evaluation of blended tender coconut products - Shahanas E (Department of Home Science, College of Horticulture, 2014)
The present study was undertaken to standardise jam and spread using tender coconut pulp with fruit pulp and fruit extract and to evaluate the quality attributes and shelf life of the selected products. The products were standardised by incorporating tender coconut pulp at various levels with fruit pulp of pineapple, mango, grapes and papaya for jam and with the fruit extracts of guava, jack fruit rind and plantain for spread. A total of 16 treatments were tried for jam varying the quantity of tender coconut pulp (TCP) and fruit pulp at three different proportions. For spread a total of nine treatments were tried varying the quantity of TCP and fruit extract. On the basis of maximum organoleptic scores obtained, one product each from different fruit pulp and fruit extract for jam and spread respectively were selected for further studies. Thus, a total of six treatments for jam and three treatments for spread including the control prepared with 100 per cent TCP were selected for storage study. For jam, JT4 (25% TCP + 75 % pineapple Pulp), JT6 (50% TCP + 50 % mango pulp), JT10 (25% TCP + 75 % grape pulp), JT11 (75% TCP + 25 % papaya pulp) and JT16 (25% TCP + 75 % blended fruit pulp) and for spread ST3 (25% TCP + 75% guava extract), ST6 (25% TCP + 75 % jack fruit rind extract) and ST8 (50% TCP + 50 % plantain extract) were selected for storage study. The selected products were stored for a period of six months and the various quality attributes were evaluated during storage. The highest gel strength for jam and spread were observed for JT16 (25% TCP + 75 % blended fruit pulp) and ST3 (25% TCP + 75% guava extract) respectively. The maximum adhesiveness was in the jam prepared using 100% tender coconut pulp. An increase in adhesiveness was evident with increase in tender coconut pulp in both the products. Acidity, moisture, TSS and reducing sugar of the products slightly increased during storage. However, a decreasing trend was observed in the case of total sugar content during storage. The highest fat content was observed in jam prepared using 100% TCP. The fat content increased with an increase in TCP content in both the products. The mineral content gradually decreased with advancement of storage period. A wide variation was noticed in the iron content of tender coconut products on the basis of fruit pulp or extract used. On the basis of nutritional qualities, jam prepared with 25% TCP and 75% pineapple pulp (JT4) and the spread prepared with 25% TCP and 75% jack fruit rind extract (ST6) were found to be the best. Jam and spread prepared using different combinations of TCP and fruit pulp/extracts were found to be organoleptically acceptable. Jam prepared with 25% TCP and 75% blended fruit pulp (JT16 ) was organoleptically the best. The spread prepared with equal quantity of TCP and plantain extract (ST8 ) obtained the maximum score for organoleptic qualities. However, all the organoleptic qualities decreased during storage in both products. No microbial contamination was noticed in both the products initially. However, at the end of storage period microbial load was detected in both products. The cost of the products per 100 g varied from Rs.19.63 to Rs.29.63 for jam and Rs. 14.63 to Rs.18.13 for spread. The residual coconut pulp left in the tender coconuts after the consumption of coconut water can be effectively utilized for the preparation of jam and spread. Blending with fruit pulp and fruit extracts increased the nutritional qualities and acceptability of the products